Career Barriers: How People Experience, Overcome and Avoid FailureCareer Barriers: How People Experience, Overcome and Avoid Failure, by LondonManuel. Mahwah, NJ: Lawrence Erlbaum Associates, 1998. - Bhagat, Rabi S. (Academy of Management Review, 1999)
The article reviews the book ?Career Barriers: How People Experience, Overcome and Avoid Failure,? by Manuel London.